Validation of joint space narrowing on plain radiographs and its relevance to partial knee arthroplasty: radiological and MRI data from the Osteoarthritis Initiative. Issue 3 (1st March 2021) - Khury, Farouk; Fuchs, Michael; Awan Malik, Hassan; Leiprecht, Janina; Reichel, Heiko; Faschingbauer, Martin
Abstract : Aims: To explore the clinical relevance of joint space width (JSW) narrowing on standardized-flexion (SF) radiographs in the assessment of cartilage degeneration in specific subregions seen on MRI sequences in knee osteoarthritis (OA) with neutral, valgus, and varus alignments, and potential planning of partial knee arthroplasty. Methods: We retrospectively reviewed 639 subjects, aged 45 to 79 years, in the Osteoarthritis Initiative (OAI) study, who had symptomatic knees with Kellgren and Lawrence grade 2 to 4. Knees were categorized as neutral, valgus, and varus knees by measuring hip-knee-angles on hip-knee-ankle radiographs. Femorotibial JSW was measured on posteroanterior SF radiographs using a special software. The femorotibial compartment was divided into 16 subregions, and MR-tomographic measurements of cartilage volume, thickness, and subchondral bone area were documented. Linear regression with adjustment for age, sex, body mass index, and Kellgren and Lawrence grade was used. Results: We studied 345 neutral, 87 valgus, and 207 varus knees. Radiological JSW narrowing was significantly (p < 0.01) associated with cartilage volume and thickness in medial femorotibial compartment in neutral ( r = 0.78, odds ratio (OR) 2.33) and varus knees ( r = 0.86, OR 1.92), and in lateral tibial subregions in valgus knees ( r = 0.87, OR 3.71). A significant negative correlation was found between JSW narrowing and area of subchondral bone in external lateral tibial subregion in valgus knees ( r = −0.65, p < 0.01) and in external medial tibial subregion in varus knees ( r = −0.77, p < 0.01). No statistically significant correlation was found in anterior and posterior subregions. Conclusion: SF radiographs can be potentially used for initial detection of cartilage degeneration as assessed by MRI in medial and lateral but not in anterior or posterior subregions. Cite this article: Bone Joint Res  2021;10(3):173–187.